Comparing the Combined Effect of Garlic and Mint Extract with Metronidazole in Helicobacter Pylori Treatment: Garlic and Mint in Helicobacter Pylori Treatment - Ghorban-Ali Rahimian,; Bahram Tahmasebi,; Zahra Rabiei,; Mahmoud Rafieian-Kopaei,; Foroozan Ganji,; Razieh Rahimian,; Abulghasem sharifi, (Iranian Journal of Pharmaceutical Sciences, 2013)
Helicobacter pylori infection is one of the most common human infections which have been associated with many upper gasterointestinal complications. Different treatment regimens for Helicobacter pylori eradication have been used. One of these regimes is the quadruple therapy regimen which metronidazole is one of the medications. In recent years several reports on H. pylori resistance to this antibiotic has been presented. This study was performed to compare the effects of garlic and peppermint extract combination with metronidazole in the treatment of Helicobacter pylori infection. In this randomized double blind clinical trial, 142 patients who were eligible for inclusion in study after completing the questionnaire and consent form were randomly divided into two groups, receiving garlic and peppermint extract or metronidazole. Moreover, for both groups the drugs; amoxicillin, omeprazole and bismuth were also administrated. Two weeks after drug administration completion, urease breath test (UBT) was performed and based on the obtained data, the recovery rate in the two groups were compare using SPSS 16 software T-test and Ki squire. The patients mean age was 43.89± 13.37 years. Evaluating the age and sex factors, we found no significant difference between two groups. Results suggest that although the combination of amoxicillin, omeprazole, bismuth plus garlic and peppermint was not successful in the eradication of Helicobacter pylori such as the quadruple therapy, but less than half of cases lead to eradication of Helicobacter pylori infection.